2009
DOI: 10.1253/circj.cj-08-0940
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Myocardial Ischemia Using 64-Slice MDCT

Abstract: Background:The purpose is to investigate the ability of 64-slice multidetector computed tomography (MDCT) at rest in detecting myocardial ischemia, conventionally depicted by myocardial perfusion scintigraphy (MPS). Methods and Results:In 75 patients with suspected coronary artery disease, cardiac CE-MDCT at rest and stress/rest MPS were performed. The 2D myocardial images were reconstructed in diastolic and systolic phases using raw data from coronary computed tomography (CT) angiography. CT numbers in the my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
1
18
0
5
Order By: Relevance
“…Multidetector computed tomography (MDCT) has been used as a valuable non-invasive tool for evaluation of coronary artery atherosclerotic plaque. 8- 14 Furthermore, recent developments in MDCT technology, including increased detectors and dedicated coronary artery analysis software, have enabled sophisticated volumetric plaque analysis on intravascular ultrasound (IVUS). 15, 16 We therefore reasoned that MDCT can provide additional information beyond coronary angiography, and can predict the success of CTO PCI.…”
mentioning
confidence: 99%
“…Multidetector computed tomography (MDCT) has been used as a valuable non-invasive tool for evaluation of coronary artery atherosclerotic plaque. 8- 14 Furthermore, recent developments in MDCT technology, including increased detectors and dedicated coronary artery analysis software, have enabled sophisticated volumetric plaque analysis on intravascular ultrasound (IVUS). 15, 16 We therefore reasoned that MDCT can provide additional information beyond coronary angiography, and can predict the success of CTO PCI.…”
mentioning
confidence: 99%
“…Our results showed that severe coronary calcification was the leading cause of nonevaluable coronary segments on CCTA, with a specificity of 69% and a PPV of 81% in the per-vessel analysis compared with ICA for detecting angiographically significant stenoses. Although the capability of resting CCTA for detecting myocardial ischemia remains debatable [35], CCTA does not reliably provide the physiological significance of coronary stenoses [36]. In our series, ICA revealed stenosis ≥50% in 168 (88%) and hemodynamically significant stenosis in 144 (75%) patients.…”
Section: Discussionmentioning
confidence: 58%
“…Nagao et al 69 had earlier described myocardial ischaemia as a characteristic enhancement pattern, by correlating colour-coded rest cCTA studies to SPECT images and had correctly identified myocardial ischaemia in 36 of 40 patients (90%), with a specificity of 83%, a PPV of 86% and a NPV of 88%. In a separate investigation in a population of 20 patients, the same group reported 16 perfusion defects at rest CTA that were not detected on resting SPECT, 8 of which, however, became apparent on stress SPECT.…”
Section: Ct Acquisition At Restmentioning
confidence: 99%